2017
DOI: 10.1002/jbm.a.36077
|View full text |Cite
|
Sign up to set email alerts
|

Polyester fibers can be rendered calcium phosphate‐binding by surface functionalization with bisphosphonate groups

Abstract: Fibers are often used as structural elements to improve the mechanical properties of materials such as brittle ceramic matrices by facilitating the dissipation of energy. However, this energy dissipation is mainly controlled by the interface between the two components, and a poorly designed fiber-matrix interface strongly reduces the efficacy of fiber reinforcement. Here, we present a versatile approach to control the affinity of biocompatible fibers to calcium-containing matrices to maximize the efficacy of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…A smaller number of studies is related to the surface functionalization of other polyesters, such as polylactide [36,37,38] and poly(lactide- co -caprolactone) [19,39,40,41]. Moreover, in the case of PLLA meshes, aminolysis is frequently used as a method of fiber fragmentation [42,43,44,45,46]. The aim of our paper is to explain the different efficiency of the aminolysis at the same processing conditions for various aliphatic polyesters in the form of nanofibers and films.…”
Section: Introductionmentioning
confidence: 99%
“…A smaller number of studies is related to the surface functionalization of other polyesters, such as polylactide [36,37,38] and poly(lactide- co -caprolactone) [19,39,40,41]. Moreover, in the case of PLLA meshes, aminolysis is frequently used as a method of fiber fragmentation [42,43,44,45,46]. The aim of our paper is to explain the different efficiency of the aminolysis at the same processing conditions for various aliphatic polyesters in the form of nanofibers and films.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, frictional sliding operates mainly at the interface between the fiber and the matrix and plays an important role in the effective stress transfer between the two constituents so that more energy is dissipated and less fractures occur. 63…”
Section: Results and Discussionmentioning
confidence: 99%
“…2d, the presence of the P 2p signals at 134 eV further demonstrated that bisphosphonate groups were successfully introduced into GelMA. Thus, the FTIR, 1 H NMR, 31 P NMR and XPS data demonstrated that alendronate was successfully grafted onto GelMA.…”
Section: Characterization Of Gelma and Gelma-alnmentioning
confidence: 90%
“…27,28 Furthermore, BP groups strongly and reversibly bind calcium ions 29,30 and can also bind to hydroxyapatite, calcium phosphate and other calcium crystals. 31,32 BP groups were shown to have a high affinity for bone minerals, which leads to their selective uptake by bone. 33 Although the activity [34][35][36][37][38][39] and osteogenesis [40][41][42][43][44][45] of cells encapsulated in 3D GelMA hydrogels have been widely studied, fewer studies have focused on the osteogenesis of cells cultured in 3D BP-functionalized hydrogels.…”
Section: Introductionmentioning
confidence: 99%